Employee Performance In Terms Of Leadership And Organizational Culture Aspects - Kukuh Kridantoro; Edy Suwasono; Ratna Dewi Mulyaningtiyas; Eka Askafi (Cita Konsultindo Research Center, 2023)
The aim of this study was to investigate the factors that can influence employee performance, such as leadership and organizational culture. The research adopted a quantitative approach, and a sample of 88 respondents was used. Data analysis was carried out using SPSS Version 24 for Windows. The findings of the study revealed significant effects of both leadership and organizational culture on employee performance. Interestingly, organizational culture was found to have a more significant impact on employee performance compared to the leadership variable..